LIVESTOCK PRODUCTION CONTRIBUTIONS TO RURAL HOUSEHOLDS’ LIVELIHOOD AND ITS CONSTRAINTS IN NIGER STATE, NIGERIA - Mathias Ofonedu UMUNNA; Azeez Olalekan IBRAHIM; Oluwasegun Mobolaji SODIYA; Emmanuel Olushola ADEDEJI; Olorunfemi Boye OYEDIRAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper considered the livestock production contributions to rural households’ livelihood and its constraints in Niger State, Nigeria. The data used were primary while the interview schedule was used to collect data from the 120 households. The paper engaged a quantifiable analysis using the descriptive and inferential statistics. The analysis revealed that households’ socio-economic characteristics such as sex (χ2 =9.362; p<0.05), marital status (χ2=56.06; p<0.05), educational level (χ2=18.367; p<0.05) and the constraints of livestock production (χ2= 9.362; p<0.05) among the households are associated factors to the contributions of livestock production the households. These circumstances led to the age (r = 0.267; p<0.05), household size (r =-0.053; p<0.05), years of experience in livestock production (r = 0.204; p<0.05) and monthly income generated (r =0.080; p<0.05) having a significant relationship with the contributions of livestock production to the respondents’ households. Based on the findings of this study, it was recommended that households should be encouraged in livestock production through provision of credit facilities, veterinary services and extension in order to contribute to the livelihoods of the households.